Penggunaan Algoritma random forest dan Agile scrum dalam Pengembangan Aplikasi Kesehatan mental Berbasis Web 'MentalWell' - Masbahah, M; Putri, Azzahra Kareena Rendri; Lathifa, Diana; Nawang, Diah Munica; Anshori, Fauzi Ihsan; Kusnadi, Bimo Adji (LPPM STIKOM Tunas Bangsa, 2024)
Teenage mental health is a major concern today. Teenagers often suffer from various mental health problems such as depression, anxiety, and stress, which can have a negative impact on their development and lives. The aim of this research was to develop a mental health website that helps adolescents identify and overcome mental health problems. The